Development and optimization of a biological protocol for DNA detection of escherichia coli O157:H7 by quartz crystal microbalance with dissipation (QCM-D) - Rodrigues, Raquel Oliveira (2013)
Escherichia coli O157:H7 is a foodborne pathogen associated to outbreaks with high mortality. Since the traditional methods for its detection are often time-consuming, there is a need to develop new techniques that allow a rapid, simple, reliable, specific and sensitive detection. The present study aimed to develop a biological protocol for DNA detection of Escherichia coli O157:H7 using a Quartz Crystal Microbalance with Dissipation (QCM-D), to be applied as a genosensor. DNA thiol Probes and the respective DNA Target were selected from the eae gene of E. coli O157:H7. Several parameters (such as, concentration, incubation time and temperature) were studied and optimized, on the steps of DNA thiol Probes immobilization, 6-Mercapto-1-hexanol (MCH) blocking agent deposition and DNA Target hybridization. Both the DNA probe and target oligonucleotides were linked to fluorochromes allowing the use of Epifluorescence microscopy, to verify the mass deposition results obtained by the QCM-D device, in the gold electrode. In this study, the best results regarding immobilization on the gold electrode at 22ºC were obtained using 1.00 μM of DNA probe and 30 minutes of incubation. MCH blocking agent was prepared with 1x TE buffer instead of Milli-Q water, and best results were achieved with 1.00 mM and 30 minutes of incubation. Co-immobilization of DNA thiol probes with MCH did not reveal a significant improvement compared with the separated steps. An increase in the quantity of target DNA detected in the gold electrode was observed when using 1.00 μM target DNA at 30ºC, however the analysis of the Epifluorescence microscope images indicate that this increase is possibly related with non-specific immobilization instead of hybridization efficiency increase. Escherichia coli O157:H7 é um microrganismo patogénico associado a surtos alimentares com elevada mortalidade. Considerando que os métodos tradicionais de deteção são demasiado morosos, torna-se necessário desenvolver novas técnicas que permitam uma rápida, simples, fiável, específica e sensível deteção. O presente trabalho teve como objetivo, o desenvolvimento de um protocolo biológico para a deteção de ADN de Escherichia coli O157:H7 usando uma Microbalança de Cristal de Quartzo com factor de Dissipação (QCM-D), de forma a ser aplicado como um genossensor. As sondas tioladas de ADN e, respetivo ADN complementário, foram selecionadas a partir do gene eae de E. coli O157:H7. Foram estudados e otimizados vários parâmetros (concentração, tempo de incubação e temperatura) nos passos de imobilização de sondas tioladas de ADN, de deposição de 6-Mercapto-1-Hexanol (MCH) e hibridação de ADN complementar. Foram adicionados fluorocromos às sondas tioladas de ADN e ADN complementar, para a verificação dos resultados obtidos em massa a partir da QCM-D por microscopia de epifluorescência. Neste estudo, os melhores resultados relativamente à imobilização das sondas de ADN foram conseguidos com 1.00 μM de concentração e tempo de imobilização de 30 minutos. O agente bloqueador (MCH) foi preparado em tampão 1x TE e os melhores resultados foram alcançados com 1.00 mM e 30 minutos de incubação. A co-imobilização de sondas de ADN com MCH não mostrou melhorias significativas. Usando 1.00 μM de ADN complementar a 30ºC, observou-se um aumento da quantidade de ADN depositado no eléctrodo de ouro, contudo as imagens obtidas por microscopia de epifluorescência mostraram que este aumento pode ser devido a imobilização inespecífica e não por aumento da eficiência de hibridação.